Paideia: The World of the Second Sophistic - Borg, Barbara E. (Millennium-Studien / Millennium Studies, 2008)
In the World of the Second Sophistic, the Roman Empire's Greek elite turned education, paideia, and knowledge of the Classical age into a vital factor in their struggle for political power. This book presents, for the first time, studies from a broad range of disciplines on various fields of life and on different media, in which this ideology became manifest.